Toward Sustainable Rural Ecotourism Evolution: The Case Of Kiskan, Iran - Soroush Khalili; Pegah Moridsadat; Hamid Soltaninejad (Geography, Environment, Sustainability, 2020)
In Iran, due to the multiplicity, diversity and cultural-natural potential of rural areas, developing ecotourism is accepted as a key solution to sustainable rural development. The government putting strong emphasis on analysing the capacities and obstacles of promoting rural tourism in order to making effective strategies. Kiskan Rural District (KRD) in Kerman Province has great potential for ecotourism development to diversify rural economy, employment and income generation. So the purpose of this study is to investigate the rural ecotourism situation of KRD through SWOT analysis. It is an applied research that uses documentary and field methods including observation, unstructured interview and a questionnaire to data gathering. A group of local managers, counting Village Council Members and Rural Mayors, were selected by snowball sampling method. To this end, the status of rural ecotourism in KRD is determined and the weight of each of the four SWOT factors is measured. Results show that KRD ecotourism development strategy is «SO» (aggressive), which should exploit the strengths to take advantage of the available opportunities.